Effect of solution treatment under load on microstructure and fabrication of porous NiTi shape memory alloy by self-propagating high temperature synthesis - Kaya, M.; Orhan, N.; Kurt, B. (Taylor & Francis Ltd, 2009)
Porous NiTi shape memory alloy was fabricated by self-propagating high temperature synthesis. Effects of solution treatment under load applied on the microstructure were investigated. The densities of the phases changed insignificantly with solution treatment but the intermetallic phases such as Ti2Ni, Ni4Ti3 and Ni3Ti2 disappeared and the density of B2(NiTi) phase increased with the load applied during solution treatment. Consequently, porous NiTi SMA with ideal pore characteristics, high chemical homogeneity and high strength for hard tissue implants was obtained.
Keywords: NiTi; Shape memory alloys; Porous materials; Self-propagating high temperature synthesis